Perbandingan Pemahaman Konsep Siswa Pada Pembelajaran Impuls Dan Momentum Menggunakan Media Animasi 3D dengan 2D - Haditya Aprita Lora; Feriansyah Sesunan; Ismu Wahyudi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This research aims to know a better concept comprehension between using 3D animation learning media with 2D on Impuls and Momentum learning and describe the concept comprehension on both treatments. The research method used is quantitative and descriptive. The research data was obtained through multiple choice test with the certainty of response index (CRI) answer sheet. The research design used was Pretest-Posttest Equivalent Group Design with a sample of two experimental classes selected at random. The results using Mann Whitney U-test showed a significance value of 0.009. This shows that the students' concept comprehension using 3D animation learning media is higher than using 2D animated learning media. The concept comprehension of students who understand the concept of the class using 3D animation media that is 41.99%, while the class that uses 2D animation media is 34.38%. For the misconception level in the classroom that uses 3D animation media that is 41.02%, while the class that uses 2D animation media is 43.95%.